Long-Term Effects of Prenatal Exposure to Undernutrition on Cannabinoid Receptor-Related Behaviors: Sex and Tissue-Specific Alterations in the mRNA Expression of Cannabinoid Receptors and Lipid Metabolic Regulators - Ramírez-López, María T.; Arco, Rocío; Decara, Juan; Vázquez, Mariam; Rivera, Patricia; Blanco, Rosario Noemi; Alén, Francisco; Gómez de Heras, Raquel; Suárez, Juan; Rodríguez de Fonseca, Fernando (Frontiers in Behavioral Neuroscience, 2016)
Maternal malnutrition causes long-lasting alterations in feeding behavior and energy homeostasis in offspring. It is still unknown whether the endocannabinoid (eCB) machinery and the lipid and cholesterol metabolism are implicated in long-term adaptive responses to fetal reprogramming caused by maternal undernutrition. We investigated the long-term effects of maternal exposure to a 20% standard diet restriction during preconceptional and gestational periods on the metabolically-relevant tissues hypothalamus, liver and perirenal fat (PAT) of male and female offspring at adulthood. The adult male offspring from calorie-restricted dams (RC males) exhibited an increase in body weight, perirenal adiposity, AM251-induced restriction in total caloric intake, and plasma levels of triglycerides, LDL, VLDL, bilirubin and leptin. The gene expression of the cannabinoid receptors Cnr1 and Cnr2 was increased in RC male hypothalamus, but a down-expression of most eCBs-metabolizing enzymes (Faah, Daglα, Daglβ, Mgll) and several key regulators of fatty-acid β-oxidation (Cpt1b, Acox1), mitochondrial respiration (Cox4i1) and lipid flux (Pparγ) was found in their PAT. The female offspring from calorie-restricted dams exhibited higher plasma levels of LDL and glucose as well as a reduction in chocolate and caloric intake at postweaning periods in the feeding tests. Their liver showed a decreased gene expression of Cnr1, Pparα, Pparγ, the eCBs-degrading enzymes Faah and Mgll, the de novo lipogenic enzymes Acaca and Fasn, and the liver-specific cholesterol biosynthesis regulators Insig1 and Hmgcr. Our results suggest that the long-lasting adaptive responses to maternal caloric restriction affected cannabinoid-regulated mechanisms involved in feeding behavior, adipose β-oxidation and hepatic lipid and cholesterol biosynthesis in a sex-dependent manner.